Empowering Classroom Interaction: Innovative Teaching Techniques by English Teachers at Islamic High School Students - Hasanudin, Hasanudin; A, Yuliana; Akib, Rizall; Hikmawati, Agci; Sara Sehwaky, Wahyuni (JULIET: Journal of English Language and Literature, 2025)
This study explores the effectiveness of innovative teaching techniques in enhancing classroom interaction and student engagement in an Islamic high school setting. Employing a qualitative research approach, observations and interviews were conducted with English teachers and students at SMA Islam Guppi in Kota Sorong. The findings reveal that structured explanations, interactive learning through questioning and group work, effective classroom management, positive reinforcement, and task-based learning contribute significantly to student motivation and participation. These techniques align with key educational theories, such as Vygotsky’s Zone of Proximal Development, Mercer’s Sociocultural Theory, and Schunk’s Self-Regulated Learning Theory. The study underscores the importance of adaptable teaching strategies that accommodate diverse learning needs and foster an engaging educational environment.